MEMBANGUN MASA DEPAN: KIPRAH PC PPM CIAMIS DALAM GIAT TNI MANUNGGAL MEMBANGUN DESA (EKSISTENSI ORGANISASI DAN PENAAMAN NILAI NASIONALISME) - Widaningsih (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2025)
This study examines the role of the Ciamis Panca Marga Youth Branch Leadership (PC PPM) in the TNI Manunggal Membangun Desa (TMMD) program as a form of strengthening the organization's existence and instilling nationalist values. Through active involvement in both physical and non-physical activities, PPM Ciamis demonstrates a strategic role in village development, assisting the community, and bridging communication between the TNI and residents, especially the younger generation. The method used is descriptive qualitative through interviews, observation, and documentation. The results show that the role of PC PPM Ciamis in the TMMD program clearly reflects the practice of national values ​​and a strong spirit of nationalism. Through mutual cooperation and community service, this organization proves its existence not only as a symbolic entity, but as an agent of change that contributes directly to village development.